2008
DOI: 10.1111/j.1439-0272.2008.00845.x
|View full text |Cite
|
Sign up to set email alerts
|

Screening for bacterial pathogens in semen samples from infertile men with and without leukocytospermia

Abstract: We aimed to study the correlation between leukocyte counts in semen and bacterial pathogens in seminal samples of infertile men, and to establish the minimum leukocyte count associated with significant bacteriospermia. A total of 116 patients who underwent evaluation of fertility were investigated using routine semen analysis according to the guidelines of the WHO and bacterial pathogens analysis by culture and in-house PCR assay. The overall prevalence of bacteriospermia in semen samples was 56.9% independent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
3
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 51 publications
4
35
3
1
Order By: Relevance
“…The prevalence of bacteriospermia in semen samples varies across different studies -51% (5) in Cottell et al's study, 35.7% (4) and 51.1% (6) in Lackner et al's studies, 56.9% (7) in Gdoura et al's study, and 63.9% (11) in Rodin et al's study. The prevalence of bacteriospermia in the present study was 18.6%, which is much lower than those previously reported.…”
Section: This Methods Proved Effective As None Of Their Cultures Hadmentioning
confidence: 87%
See 3 more Smart Citations
“…The prevalence of bacteriospermia in semen samples varies across different studies -51% (5) in Cottell et al's study, 35.7% (4) and 51.1% (6) in Lackner et al's studies, 56.9% (7) in Gdoura et al's study, and 63.9% (11) in Rodin et al's study. The prevalence of bacteriospermia in the present study was 18.6%, which is much lower than those previously reported.…”
Section: This Methods Proved Effective As None Of Their Cultures Hadmentioning
confidence: 87%
“…We feel that an increased PMN count is not an indicator for antibiotic treatment, and that anti-inflammatory agents may be effective in lowering the PMN count. Also, reactive oxygen species, proteases and cytokines resulting from an increased PMN count have been considered the mechanism of sperm damage in a study by Gdoura et al (7) Using a COX-2 inhibitor, Lackner et al were able to reduce leucocytospermia and increase sperm count in patients with abacterial leucocytospermia. (4) In sexual reproduction, the female genital tract has lysozymes, phagocytes and lactic acid, which function as a natural defence mechanism against microbial infection from semen.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, Punab et al observed a positive correlation between the leukocyte count and the number of different bacteria detected in semen, and also between the leukocyte count and the total count of microorganisms in semen samples [77]. In fact, these authors along with Gdoura et al [78] demonstrated that the WHO-defined cut-off point (1x10 6 leukocytes per mL) has very low sensitivity for discriminating between patients with and without significant bacteriospermia, as a more optimal sensitivity/specificity ratio appears at 0.2x10 6 leukocytes per mL of semen.…”
Section: The Controversial Role Of Leukocytospermia On Fertilitymentioning
confidence: 88%